The effect of exercise on autophagy receptors and ubiquitin-dependent mitophagy pathway: Narrative review - Samaneh Eidel; Morteza Movahedizadeh; Ali Fakourian; Fatemeh Rostamkhani (Journal of Exercise & Organ Cross Talk)
Most of the intracellular and extracellular factors that play a vital role in regulating energy metabolism and determining cell fate converge in the mitochondria. To promote or hinder cell survival through regulating the function and maintaining the mitochondrial structure. The decline of mitochondrial function and homeostasis with aging is the basis of the pathogenesis of aging-related diseases, especially in skeletal muscles. One of the important components of mitochondrial quality control that helps maintain the homeostasis of myocytes is autophagy, which is an important biological and evolutionary process, and its vital function is the removal of defective organelles. Although it has been proven that regular sports activities act as autophagy stimulators and play a role in maintaining the cellular homeostasis of skeletal muscle fibers and regulating intracellular metabolism. However, cellular autophagic responses to exercise in skeletal muscle appear to be different in different exercise protocols and disease models. How exercise activity modulates autophagy in skeletal muscle and how the effect of exercise is regulated by the autophagy signaling pathway are still poorly understood. The importance of understanding the obscure angles of this process can be an important goal in preventing the pathology of age-related diseases in skeletal muscle.